2023
DOI: 10.3390/ani13040548
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combining Millet and Corn Straw as Source Forage for Beef Cattle Diets on Ruminal Degradability and Fungal Community

Abstract: Three ruminal cannulated Simmental crossbreed bulls (approximately 3 years of age and with 380 ± 20 kg live weight at initiation of the experiment) were used in a 3 × 3 Latin square experiment in order to determine the effects of the treatments on ruminal pH and degradability of nutrients, as well as the rumen fungal community. The experimental periods were 21 d, with 18 d of adjustment to the respective dietary treatments and 3 d of sample collection. Treatments consisted of a basal diet containing a 47.11% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…When animals age, parasitic infections, traumatic injuries, and other diseases cause their immune function to decrease, making them susceptible to infection by potentially pathogenic fungi. All five groups of samples contained Thelebolus, which was the genera; similar findings were reported in yak (Zhu et al, 2023) and beef cattle (Tong et al, 2023) under different feeding patterns. Thelebolus negatively impacts ruminant health and behavior (Koester et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…When animals age, parasitic infections, traumatic injuries, and other diseases cause their immune function to decrease, making them susceptible to infection by potentially pathogenic fungi. All five groups of samples contained Thelebolus, which was the genera; similar findings were reported in yak (Zhu et al, 2023) and beef cattle (Tong et al, 2023) under different feeding patterns. Thelebolus negatively impacts ruminant health and behavior (Koester et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…We found that the genus Thelebolus was the most dominant in Korean wild long-tailed gorals. Thelebolus is known to be dispersed by animals [ 47 ], and it is closely related to wild animals and dominant in some ruminants [ 48 ]. Considering that it makes up nearly half of the sequences obtained from the gut eco-information of wild long-tailed gorals, it can be seen as evidence that wild long-tailed gorals are excellent Thelebolus dispersers that have a significant impact on the ecology and evolution of this genus of soil fungus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, because of the conventional viewpoint in the bacteria as the primary functional microorganisms of rumen, the majority of studies focused on the bacterial composition in the rumen of ruminants (Ma et al 2020 ; Zhang et al 2023 ). In fact, the fungal community acts as an essential role in the digestion of cellulose (Tong et al 2023 ). Therefore, in the current study, we performed an in vitro experiment to assess the influence of YC supplementation levels on ruminal fermentation profile and bacterial and fungal community of high concentrate diet in sheep.…”
Section: Introductionmentioning
confidence: 99%